2019
DOI: 10.24990/injec.v4i1.241
|View full text |Cite
|
Sign up to set email alerts
|

Gen Z Nursing Students' Usage, Perception and Satisfaction With Facebook for Educational Purposes: Tool for Learning or Distraction

Abstract: Introduction: Gen Z has started to enter the portals of nursing classrooms. They are technology and socially-savvy consumers who grew up in the world of internet and smartphones. However, little is known about this generation, particularly among nursing students and how they use Facebook for academic purposes. The purpose of this study was to determine nursing students’ usage, perception, and satisfaction with Facebook for educational purposes Methods:A descriptive, cross-sectional research design was used. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…5). These findings are consistent with Oducado (2019) who observed that Gen Z use social media to communicate, collaborate and share academic sources or materials. In addition, Turner (2015) emphasized that Gen Z preferred to have multiple streams of information, regular and rapid interactions with data, technical and interactive experiences that demonstrate specific goals, increase motivation, and involve authentic activities.…”
Section: Social Media Usage For Education (H 4 )supporting
confidence: 90%
“…5). These findings are consistent with Oducado (2019) who observed that Gen Z use social media to communicate, collaborate and share academic sources or materials. In addition, Turner (2015) emphasized that Gen Z preferred to have multiple streams of information, regular and rapid interactions with data, technical and interactive experiences that demonstrate specific goals, increase motivation, and involve authentic activities.…”
Section: Social Media Usage For Education (H 4 )supporting
confidence: 90%
“…Meanwhile, the hesitation of faculty toward online education may also be related to the fact that the majority had a somewhat stable Internet connection, and only a few faculty in this study had a very stable connection. Even among college students, Internet connectivity remains to be an issue [7]. The Philippines is known to have the worst and slowest Internet connection speed among Asia Pacific countries [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although according to CHED, flexible learning may not necessarily mean that instruction will be delivered purely online [5], online education is an inevitable option to decongest classrooms amid physical or social distancing protocol and help mitigate COVID-19 transmission in schools when SUCs start to open their campuses and begin classes again. While it may be argued that complete online modality of the instruction can be feasible [6] and even though Filipinos are among the top users of Internet worldwide [7], the lack of preparation of faculty members to conduct online classes along with the problem long before on poor internet connection in the country pose challenges in the adoption of online education in the Philippine context [8]. It is also contended that fully online education widens the educational and socioeconomic gap while unsuccessful in making education affordable [9].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the type of social media use, previous studies identified as the most popular Facebook, Twitter, and YouTube [3,12,15,18,19,21]. Oducado [18] studied the educational use of Facebook by Gen Z nursing students analyzing their perception and satisfaction, finding that the majority of them use it to communicate (91.15%), collaborate (87.61%), and share academic sources or materials (85.84%), and they generally were highly satisfied (77%). Nevertheless, easy distraction with other content was identified as the central trouble (81.42%) in Facebook's use for educative purposes.…”
Section: Discussionmentioning
confidence: 99%
“…A vast number of examples have been described in previous studies, such as video tutorials, YouTube ® , Facebook ® , WhatsApp ® , Twitter ® , concept mapping or infographics, hybrid or flipped classroom, storytelling, virtual learning environments, gaming, clicker technology or quizzes (Kahoot! ® , Socrative ® , Jeopardy ® ), blogs, simulations, role-playing, case study, jigsaw classroom, smartphone applications, and QR codes [1,5,6,8,11,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%